The influence of mycorrhization with Tuber melanosporum in the afforestation of a Mediterranean site with Quercus ilex and Quercus faginea - Domínguez Núñez, José Alfonso; Serrano, Jesús Selva; Barreal, José Antonio Rodríguez; González, José Antonio Saiz De Omeñaca (Forest Ecology and Management, 2006)
A Holm oak (Quercus ilex L.) and Lusitanian oak (Quercus faginea) stand establishment, mycorrhizated with black trufﬂe (Tuber melanosporum Vitt.), situated in the north of Alicante, south-eastern Spain, was analyzed during the second year of plantation. The mycorrhization improved seedling growth, especially that of the shoots, encouraged water uptake of the seedlings during the summer drought, and improved total phosphorus absorption. Tuber melanosporum was found to colonize the roots of the seedlings very successfully
Keywords: ectomycorrhiza; Nutrients; quercus faginea lamk; Quercus ilex L; Reforestation; tuber melanosporum vitt; water stress

Shoot growth efficiency and production of Quercus ilex L. in different climates - Crescente, M F; Gratani, Loretta; Larcher, Walter (Flora-Morphology, Distribution, …, 2002)
Structural and functional traits of Quercus ilex L. were monitored in plants growing in the climax area (Castelporziano, Rome; site A) and at the northern distribution limit (Nago, Trento; site B) in Italy. The most distinctive climatic differences between the two sites were duration and frequency of drought, heat spells in summer at site A, and the occurrence of frost and sub-zero temperatures in winter at site B. The potential productivity of Quercus ilex lies in its tendency to be slow growing with maximum vegetative activity from the end of April to the end of June at Castelporziano, and from the middle of May to the middle of July at Nago, when air temperatures favoured the highest photosynthetic rates (90–100%). The lower shoot biomass production at site B was due to the lower relative growth rates in shoot length (RGRl < 20%) and in shoot dry mass (RGRm <11%). The lower shoot length growth efficiency (LE < 62%) at the northern limit was related to the low temperatures in winter and beginning of spring which reduced favourable periods (<20% than site A) for photosynthetic carbon gain and growth dynamics. It resulted in a lower total leaf surface area per shoot (<60% than site A) and a reduced shoot leaf mass (<31%).
Keywords: Net photosynthesis; Phenology; Quercus ilex L; Relative growth rate; shoot length growth efficiency; shoot production

Shoot growth efficiency and production of Quercus ilex L. in different climates - Crescente, M. F.; Gratani, Loretta; Larcher, Walter (Flora-Morphology, Distribution, …, 2002)
Structural and functional traits of Quercus ilex L. were monitored in plants growing in the climax area (Castelporziano, Rome; site A) and at the northern distribution limit (Nago, Trento; site B) in Italy. The most distinctive climatic differences between the two sites were duration and frequency of drought, heat spells in summer at site A, and the occurrence of frost and sub-zero temperatures in winter at site B. The potential productivity of Quercus ilex lies in its tendency to be slow growing with maximum vegetative activity from the end of April to the end of June at Castelporziano, and from the middle of May to the middle of July at Nago, when air temperatures favoured the highest photosynthetic rates (90–100%). The lower shoot biomass production at site B was due to the lower relative growth rates in shoot length (RGRl < 20%) and in shoot dry mass (RGRm <11%). The lower shoot length growth efficiency (LE < 62%) at the northern limit was related to the low temperatures in winter and beginning of spring which reduced favourable periods (<20% than site A) for photosynthetic carbon gain and growth dynamics. It resulted in a lower total leaf surface area per shoot (<60% than site A) and a reduced shoot leaf mass (<31%).
Keywords: Net photosynthesis; Phenology; Quercus ilex L; Relative growth rate; shoot length growth efficiency; shoot production

Leaves of Quercus ilex L. as biomonitors of PAHs in the air of Naples (Italy) - Alfani, Anna; Maisto, Giulia; Vittoria Prati, Maria; Baldantoni, Daniela (Atmospheric Environment, 2001)
Polycyclic aromatic hydrocarbons (PAHs)were determined by the GC-MS chromatography in the leaves of Quercus ilex L., an evergreen Mediterranean oak, to monitor the degree of pollution in the urban area of Naples compared to remote areas. Leaf samples were collected in July 1998 from four urban parks, six roadsides and two sites in remote areas. The total PAH contents in Q. ilex leaves ranged from 106.6 in a control site to 4607.5 ng/g d.w. along a road with a high tra$c #ow. The mean concentration factors (urban/control)were 3.8 for the parks and 15 for the roads. The contribution of carcinogenic PAHs (benz[a]anthracene, benzo[b]#uoranthene, benzo[k]#uoranthene, benzo[a]pyrene, dibenz[a,h]anthracene, indeno[1,2,3-c,d]pyrene)was higher in urban area and di!ered according to the site, ranging from 6.7% to 21.3%. The total PAH burden in control sites was dominated by the low molecular weight PAHs, whilst along the urban roads #uoranthene, pyrene and benz[a]anthracene among the measured PAHs showed the highest values. PAHs were positively correlated (P(0.01)to trace metals measured in a previous study.
Keywords: biomonitoring; leaves; polycyclic aromatic hydrocarbons; Quercus ilex L; rural and urban areas

Leaves of Quercus ilex L. as biomonitors of PAHs in the air of Naples (Italy) - Alfani, Anna; Maisto, Giulia; Vittoria Prati, Maria; Baldantoni, Daniela (Atmospheric Environment, 2001)
Polycyclic aromatic hydrocarbons (PAHs)were determined by the GC-MS chromatography in the leaves of Quercus ilex L., an evergreen Mediterranean oak, to monitor the degree of pollution in the urban area of Naples compared to remote areas. Leaf samples were collected in July 1998 from four urban parks, six roadsides and two sites in remote areas. The total PAH contents in Q. ilex leaves ranged from 106.6 in a control site to 4607.5 ng/g d.w. along a road with a high tra$c #ow. The mean concentration factors (urban/control)were 3.8 for the parks and 15 for the roads. The contribution of carcinogenic PAHs (benz[a]anthracene, benzo[b]#uoranthene, benzo[k]#uoranthene, benzo[a]pyrene, dibenz[a,h]anthracene, indeno[1,2,3-c,d]pyrene)was higher in urban area and di!ered according to the site, ranging from 6.7% to 21.3%. The total PAH burden in control sites was dominated by the low molecular weight PAHs, whilst along the urban roads #uoranthene, pyrene and benz[a]anthracene among the measured PAHs showed the highest values. PAHs were positively correlated (P(0.01)to trace metals measured in a previous study.
Keywords: biomonitoring; leaves; polycyclic aromatic hydrocarbons; Quercus ilex L; rural and urban areas

EMISSION OF SHORT CHAINED ORGANIC ACIDS , ALDEHYDES AND MONOTERPENES FROM QUERCUS ILEX L . AND PINUS PINEA L . IN RELATION TO PHYSIOLOGICAL ACTIVITIES , CARBON BUDGET AND EMISSION ALGORITHMS - Kesselmeier, J; Bode, K; Hofmann, U; Mtjller, H; Schafer, L; Wolf, A; Ciccioli, P; Cecinato, A; Frattoni, M; Foster, P; Dutaur, L; Torreq, L (Atmospheric Environment, 1997)
We report on the emission of monoterpenes, short-chained organic acids and aldehydes from Mediterranean oak (Quercus ilex L.) and pine (Pinus pinea L.). All studies were done with dynamic cuvettes enclosing intact branches at the top of the canopy flushed with ambient air. Daily trends are compared with the photosynthetic active radiation (PAR), leaf temperature and the physiological activities of the enclosed branches, i.e. assimilation and transpiration, with special attention on the carbon budget. Oak emits monoterpenes in high amounts, up to 2% of the assimilated carbon. As compared with monoterpenes, short-chained organic acids and aldehydes are of minor importance for oak. However, on a leaf dry-weight basis equal amounts of acids and aldehydes are released from oak and pine. As pine emitted only low amounts of terpenes (below 0.2% of the assimilated carbon) the release of terpenes and oxygenated compounds is of equal importance for this species. A comparison of a modelled light and temperature driven emission with the observed volatile organic compounds (VOC) emissions showed good agreement for monoterpenes as well as for organic acids emitted in the case of oak. For pine only the release of acids showed an adequate relation to the algorithm data, whereas the terpene emissions seemed to be dominated by temperature effects
Keywords: aldehydes; carbon budget; coniferous; deciduous; light; Monoterpenes; oak; organic acids; pine; Pinus pinea L; Plant physiology; Quercus ilex L; Temperature; Volatile Organic Compounds

Self- and cross-pollination effects on pollen tube growth and seed set in holm oak Quercus ilex L (Fagaceae) - Yacine, A; Bouras, F (Ann. For. Sci., 1997)
Patterns of the self-incompatibility system have been more often described for hermaphroditic, entomophilous and short-lived plant species. Quercus ilex is a long-lived, monoecious, anemophilous and highly self-incompatible species. We used pollination experiments to investigate phenotypic responses of the self-incompatibility system. Flowers from 14 individuals of the same stand were hand-pollinated with self-pollen, cross-pollen from a single donor and a mixture of the two types. We observed a slower pollen tube growth and no or nearly no seed production after self-pollination. The more self-pollen tubes reach the style, the more flowers will stop their ovule development, resulting in a high flower abortion rate. In open pollination, pollen load is not a limiting factor, but incompatible pollen may reach stigma simultaneously or before compatible cross-pollen, which will induce an early abortion of flowers. When pollination is qualitatively and quantitatively effective, the regulation of seed production related to the resources availability acts by the late abortion of fruit.
Keywords: pollen tube growth; Quercus ilex L; seed set; self-incompatibility

Self- and cross-pollination effects on pollen tube growth and seed set in holm oak Quercus ilex L (Fagaceae) - Yacine, A.; Bouras, F. (Ann. For. Sci., 1997)
Patterns of the self-incompatibility system have been more often described for hermaphroditic, entomophilous and short-lived plant species. Quercus ilex is a long-lived, monoecious, anemophilous and highly self-incompatible species. We used pollination experiments to investigate phenotypic responses of the self-incompatibility system. Flowers from 14 individuals of the same stand were hand-pollinated with self-pollen, cross-pollen from a single donor and a mixture of the two types. We observed a slower pollen tube growth and no or nearly no seed production after self-pollination. The more self-pollen tubes reach the style, the more flowers will stop their ovule development, resulting in a high flower abortion rate. In open pollination, pollen load is not a limiting factor, but incompatible pollen may reach stigma simultaneously or before compatible cross-pollen, which will induce an early abortion of flowers. When pollination is qualitatively and quantitatively effective, the regulation of seed production related to the resources availability acts by the late abortion of fruit.
Keywords: pollen tube growth; Quercus ilex L; seed set; self-incompatibility

Leaf and shoot growth dynamics of Quercus ilex L. - Gratani, L (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 1996)
The vegetative activity of Quercus ilex L. takes place during the period of low water stress, directly following abundant rainfall at the end of winter. Low air temperature is the limiting factor for bud opening, while high air temperature influences specific leaf area (SLA) during the growth period. Net photosynthesis and stomatal conductance increase with a rise in leaf temperature up to 25 degrees C; whereas they decrease when leaf temperature is about 30 degrees C (at the end of May) and below 18 degrees C (November). SLA increases from the low maquis to the shrubby layer of the forest in response to the decreasing irradiance. The pattern of SLA shows peak values after bud break, which then decrease to a constant value. Shrubs in the evergreen forest exhibit a high SLA in May as a result of a double increase in leaf area, while leaf dry weight changes only slighly during the first expansion. The maximum relative growth rate (RGR) in May-June causes the leaf to reach about 90% of its definitive size and structure before the period of drought stress, ensuring that leaf expansion (the time of the greatest nutritional demand) is not adversely affected. The summer air temperatures reduce the relative growth rate, but do not completely block leaf expansion until September-October. Intraspecific variation of SLA reflects the phenotypic plasticity of Quercus ilex in different habitats and demonstrates its ability to respond adequately to changing environmental factors by altering leaf morphology.
Keywords: evergreen forest; Mediterranean; Quercus ilex L

Leaf Contamination by Atmospheric Pollutants as Assessed by Elemental Analysis of Leaf Tissue, Leaf Surface Deposit and Soil - Alfani, Anna; Maisto, Giulia; Iovieno, Paola; Rutigliano, Flora a; Bartoli, Giovanni (Journal of Plant Physiology, 1996)
In order to evaluate the influence of air pollutants influx on leaf elemental composition, the concentration ofN, S, Cu, Fe and Pb were analyzed in the surface deposit and tissue of Quercus ilex L. leaves from 8 sites of the urban area of Naples. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total contents of Nand S and for available contents ofCu, Fe and Pb. In the leafsurface deposit S content was high though significantly (P<O.OOl) lower than in the leaf tissue, whilst N was not detectable. Cu, Pb and Fe contents in leafsurface deposit were conspicuous. The Pb content was higher in the leafsurface deposit than in the leaf tissue. No correlation between leaftissue and surface deposit contents was found for S or for Fe. By contrast, positive and significant correlations (P < 0.01) were found between leaf deposit and leaf tissue for both Cu and Pb. Nand S contents in the leaves were not correlated to the respective contents in the soil and the same was also found for Cu and Fe. In contrast with the presence of limiting concentrations in the soil, N, S and Fe leaf contents were significantly higher than in the leaves from remote sites. The data suggest that direct uptake of airborne pollutants, in addition to root absorption, may influence leaf elemental composition of Q. ilex L. leaves.
The following values have no corresponding Zotero field: publisher: Gustav Fischer Verlag, Stuttgart
Keywords: air pollution; leaf contamination; nitrogen; Quercus ilex L; sulphur; Trace metals

Leaf Contamination by Atmospheric Pollutants as Assessed by Elemental Analysis of Leaf Tissue, Leaf Surface Deposit and Soil - Alfani, Anna; Maisto, Giulia; Iovieno, Paola; Rutigliano, Flora a.; Bartoli, Giovanni (Journal of Plant Physiology, 1996)
In order to evaluate the influence of air pollutants influx on leaf elemental composition, the concentration ofN, S, Cu, Fe and Pb were analyzed in the surface deposit and tissue of Quercus ilex L. leaves from 8 sites of the urban area of Naples. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total contents of Nand S and for available contents ofCu, Fe and Pb. In the leafsurface deposit S content was high though significantly (P<O.OOl) lower than in the leaf tissue, whilst N was not detectable. Cu, Pb and Fe contents in leafsurface deposit were conspicuous. The Pb content was higher in the leafsurface deposit than in the leaf tissue. No correlation between leaftissue and surface deposit contents was found for S or for Fe. By contrast, positive and significant correlations (P < 0.01) were found between leaf deposit and leaf tissue for both Cu and Pb. Nand S contents in the leaves were not correlated to the respective contents in the soil and the same was also found for Cu and Fe. In contrast with the presence of limiting concentrations in the soil, N, S and Fe leaf contents were significantly higher than in the leaves from remote sites. The data suggest that direct uptake of airborne pollutants, in addition to root absorption, may influence leaf elemental composition of Q. ilex L. leaves.
Keywords: air pollution; leaf contamination; nitrogen; Quercus ilex L; sulphur; Trace metals

Micrometeorological assessment of sensitivity of canopy resistance to vapour pressure deficit in a Mediterranean oak forest - Pitacco, A; Gallinaro, N (Ann. For. Sci., 1996)
Canopy surface resistance to water vapour (rc) of an extensive Quercus ilex L stand (Bosco Mesola, northeast Italy) has been evaluated by inverting the Penman-Monteith equation. The latent heat flux was estimated by applying the Bowen ratio-energy budget micrometeorological method. A linear relationship was found between rc and the vapour pressure deficit. Canopy resistance increased regularly during the day and that yielded a recurring diurnal pattern of energy partitioning where most of the latent heat was dissipated in the early morning and the release of sensible heat increased after midday. This behaviour has been confirmed also by independent estimates of transpiration, based on measurements of sap flow velocity in small branches. Ecological consequences of this feature are briefly discussed applying the concept of coupling between canopy and atmosphere
Keywords: canopy resistance; energy balance; Evapotranspiration; Quercus ilex L; sap flow

Evaluation of actual evapotranspiration of a Quercus ilex L. stand by the Bowen ratio-energy budget method - Pitacco, A; Gallinaro, N; Giulivo, C (Plant Ecology, 1992)
Actual evapotranspiration from a closed-canopy Quercus ilex L. stand has been estimated by applying the Bowen Ratio-Energy Budget method. Daily water loss was 3.5 mm day ~, with a peak rate near 0.6 mm hour ~. The phenomenon of thermal inversion, quite common in mediterranean climates, seemed to play a significant role in reducing evapotranspiration, by promoting dew formation and delaying the establishment of fluxes of latent and sensible heat away from the canopy. Dew, which may form over many hours in the night, appears to be a major sink of available energy in the early morning and may represent a useful water source for stressed foliage. The alternating processes of condensation and evaporation may have a beneficial effect on the closed stand micro-environment.
Keywords: actual evapotranspiration; bowen ratio; energy balance; Quercus ilex L

Influence of cutting methods and dates on stump sprouting in Holm oak (Quercus ilex L) coppice - Ducrey, M; Turrel, M (Ann. For. Sci., 1992)
The goals of this study were to compare height growth of stump sprouts in Quercus ilex stools cut by different methods at various times during the year. Four cutting methods were compared: chain saw at ground level and at 15 cm above ground, axe, and 'saut du piquet' ('stump breaking'). Cuttings were carried out every 2 months for a period of 1 year. Several important results can be described 4 years after cutting. Cuttings performed during the dormant season resulted in minimum stool mortality, and maximum new sprout number, height and diameter growth. An exception was cutting made during a winter frost period. Summer cuttings led to the poorest growth which, however, tended to be regained in subsequent years. Axe and chain saw cuttings yielded better results than 'saut du piquet' cutting. This last method resulted in high stool mortality and both fewer and smaller sprouts. Sprouts appeared to be more numerous and grew better when the stools initially had large and numerous shoots.
Keywords: coppice; cutting date; cutting method; Quercus ilex L; stump sprout

Organic matter distribution and fluxes within a holm oak (Quercus ilex L.) stand in the Etna volcano - LEONARDI, S.; RAPP, M.; Denes, A. (Plant Ecology, 1992)
Located at 1100 m above sea level, on the western site of the Etna volcano, the ecophysiology of the Mount Minardo holm oak coppice has been investigated for more then twenty years. In this stand, now 31 years old, the above ground biomass amounts to 15000 g m 2 of organic material, including leaves and perennial woody material. During these 31 years, the mean annual production has been around 775 g m 2. The yearly mean litterfall amounts to 310 g m 2, including 200 g m -2 of leaves, mostly two years old. The soil surface is covered by a litter layer amounting to 3150 g m-2. Each year, following Jenny's decomposition rate and field measurements, 290 g m- 2 of the litter turns into CO2, or becomes incorporated in the soil organic matter.
Keywords: Mediterranean forests; organic matter cycling; Quercus ilex L

Organic matter distribution and fluxes within a holm oak (Quercus ilex L.) stand in the Etna volcano - LEONARDI, S; Rapp, M; DENES, A (Plant Ecology, 1992)
Located at 1100 m above sea level, on the western site of the Etna volcano, the ecophysiology of the Mount Minardo holm oak coppice has been investigated for more then twenty years. In this stand, now 31 years old, the above ground biomass amounts to 15000 g m 2 of organic material, including leaves and perennial woody material. During these 31 years, the mean annual production has been around 775 g m 2. The yearly mean litterfall amounts to 310 g m 2, including 200 g m -2 of leaves, mostly two years old. The soil surface is covered by a litter layer amounting to 3150 g m-2. Each year, following Jenny's decomposition rate and field measurements, 290 g m- 2 of the litter turns into CO2, or becomes incorporated in the soil organic matter.
Keywords: Mediterranean forests; organic matter cycling; Quercus ilex L

Variations de la croissance radiale de Quercus ilex L en fonction du climat - Zhang, S H; Romane, F (Ann. For. Sci., 1991)
Diameter growth of Quercus ilex L and the interannual variability of climatic characteristics. Diameter growth of Quercus ilex L, the dominant sclerophyllous species in much of the Mediterranean basin vegetation, was studied in relation to precipitation and temperature. The study site in Montpellier (Southern France) has a Mediterranean climate. Eleven trees, grown from acorns in 1963, were cut in 1984 and the rings studied at 3 levels (ground, 0.5 and 1 m above the ground). The data were analyzed by the ARMA procedure which gives the part of the total variation due to the autocorrelation processes. A multiple regression between the factors of a principal component analysis (PCA) of the monthly climatic data (rainfall and temperature) and the residuals issuing from the ARMA procedure then suggested that the large annual rings were due to a particular rainfall distribution during the year, the late summer precipitation promoting a large annual growth diameter (table II). The presence or absence of false rings (table I) was also analyzed by PCA (figs 2 and 3). The false rings were positively correlated to a large annual growth diameter corresponding to a high summer rainfall (fig 4), while the relationship with the temperature preceding the growing season was negative. It therefore appears that this species is relatively unaffected by spring climatic conditions, ie which generally indicate the main growth phase, but that it is able to take advantage of the interannual climatic variations of the region.
Keywords: diameter growth; Mediterranean climate; Precipitation; Quercus ilex L; ring; Temperature

L'impact du déboisement sur l'azote minéral susceptible d'être absorbé par un taillis de chêne vert (Quercus ilex L) en reconstitution - Merzouki, A; Lossaint, P; Billes, G; Rapp, M (Ann. For. Sci., 1990)
The impact of deforestation on the mineral nitrogen available during restoration of the holm oak (Quercus ilex L) coppice. The impact of deforestation on the biological activity of a mediterranean red soil was studied from January 1984 to April 1986 within a holm oak (Quercus ilex L) stand after clearcut. Part of the study involved the estimation of the amount of nitrogen available for vegetation both in the mature holm oak coppice and in the 1-2-yr-old recovery stand. The study indicates that the new shoots essentially took up nitrate nitrogen; however, the mature site used both nitrate and ammonium nitrogen as nitrogen source. The availability of mineral nitrogen, essentially nitrate, ranged from 47.4 to 118.6 kg·ha -1·yr-1 in the rebuilding site and 25.6 to 63.9 kg·ha-1·yr-1 in the mature stand. At the control site, ammonium nitrogen represented 43% of the total nitrogen available.
Keywords: Deforestation; holm oak coppice; nitrate; nitrogen availability; Quercus ilex L; shoots

Local characterization of vegetation through growth forms: Mediterranean Quercus ilex coppice as an example - Floret, C; Galan, N J; Floc'h, E; Orshan, G; Romane, F (Plant Ecology, 1987)
Growth forms are considered from two viewpoints: a descriptive and a functional one. Mono-character growth forms and their biological spectra were used to test whether they can characterize certain underlying processes in Quercus ilex coppice in southern France. Correspondence analysis of 35 mono-character growth forms of 203 described taxa shows that location of renewal buds is a good integrating indicator of plant adaptations to the environment. Two of these characters (renewal bud location, Le. Raunkiaer's main life forms, and leaf consistency) appear to vary significantly along a gradient of increasing environmental constraints, especially climatic ones.
Keywords: coppice; growth form; Life form; Mediterranean climate; Quercus ilex L; Southern France